A Multiscale Model of Interleukin‐6–Mediated Immune Regulation in Crohn's Disease and Its Application in Drug Discovery and Development. (8th January 2014) - Dwivedi, G; Fitz, L; Hegen, M; Martin, SW; Harrold, J; Heatherington, A; Li, C
Abstract : In this study, we have developed a multiscale systems model of interleukin (IL)‐6–mediated immune regulation in Crohn's disease, by integrating intracellular signaling with organ‐level dynamics of pharmacological markers underlying the disease. This model was linked to a general pharmacokinetic model for therapeutic monoclonal antibodies and used to comparatively study various biotherapeutic strategies targeting IL‐6–mediated signaling in Crohn's disease. Our work illustrates techniques to develop mechanistic models of disease biology to study drug–system interaction. Despite a sparse training data set, predictions of the model were qualitatively validated by clinical biomarker data from a pilot trial with tocilizumab. Model‐based analysis suggests that strategies targeting IL‐6, IL‐6Rα, or the IL‐6/sIL‐6Rα complex are less effective at suppressing pharmacological markers of Crohn's than dual targeting the IL‐6/sIL‐6Rα complex in addition to IL‐6 or IL‐6Rα. The potential value of multiscale system pharmacology modeling in drug discovery and development is also discussed. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e89; doi:10.1038/psp.2013.64 ; advance online publication 8 January 2014